Peningkatan Wawasan Kewirausahaan Melalui Strategi Pengelolaan Dan Pengembangan Bisnis UMKM - Ferby Mutia Edwy; Inanda Shinta Anugrahani (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Empowerment and sustainability of Micro, Small and Medium Enterprises (MSMEs) is an important matter to pay attention to in order to improve people's welfare by alleviating poverty, increasing employment, and increasing people's living standards. The purpose of this community service activity is to provide socialization regarding entrepreneurial insights that focus on business management and development strategies. The methods used in this activity are situation analysis, counseling, and mentoring, as well as activity evaluation. The result of this service activity is that activity participants gain a good understanding of entrepreneurial insights through business management and development strategies so that they can maintain the continuity of their business